ANALISIS PENGARUH GOOD CORPORATE GOVERNANCE DAN MANAJEMEN LABA TERHADAP CORPORATE ENVIRONMENTAL DISCLOSUREPADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA DAN PROPER PERIODE 2012 –2014 - Wulandari Laksmi (Jurnal Ilmiah Akuntansi & Bisnis, 2016)
The trend toward environmental awareness has brought a change in attitude of orientation towards profit orientation of the company environment. Management as agents can not avoid the reality of the impact of the company’s activities were not only generate profits and raise share prices, but also have environmental impacts such as damage to ecosystems, pollution, wastewater and waste all of which are the responsibility of companies that deal with environmental aspects.This study aimed to examine the effect of earnings management and good corporate governance of the Corporate Environmental Disclosure (CED). Earnings management is measured by discretionary accruals.Population of this research are 44 mining companies listed on the Stock Exchange in 2012-2014. The data used in this study comes from the annual report and sustainability report mining companies listed on the Stock Exchange and Corporate Performance Rating Program (PROPER) in 2012 for a total of 5 companies. The sample is obtained by using purposive sampling method. Hypothesis testing method used is multiple regression analysis. The results showed that the number of audit committee meetings significantly influence the Corporate Environmental Disclosure. Meanwhile, earnings management, the proportion of independent board does not significantly influence the Corporate Environmental Disclosure. Simultaneously good corporate governance and earnings management significantly influence the Corporate Environmental Disclosure.